Granulocyte colony-stimulating factors in the prevention of febrile neutropenia: review of cost-effectiveness models. (2nd January 2017) - Fust, Kelly; Parthan, Anju; Maschio, Michael; Gu, Qing; Li, Xiaoyan; Lyman, Gary H.; Tzivelekis, Spiros; Villa, Guillermo; Weinstein, Milton C.
ABSTRACT: Introduction: We reviewed the evolution of the methods used in cost-effectiveness analyses of granulocyte colony-stimulating factors (G-CSFs) in the primary and secondary prevention of febrile neutropenia (FN) in patients receiving myelosuppressive cancer chemotherapy. Areas covered: FN is a side effect of myelosuppressive chemotherapy associated with significant morbidity, mortality, and costs. The risk of FN may depend on the drugs used within a chemotherapy regimen, and an FN event may cause chemotherapy dose reductions or delays in subsequent cycles. Expert commentary: More recent pharmacoeconomic models have reflected these clinical observations by modeling sequential chemotherapy regimens to account for FN risk on a per-cycle basis, and by accounting for chemotherapy dose reductions and consequent survival losses.